METHODS OF IMPROVING THE KNOWLEDGE AND ACTIVITY OF STUDENTS IN PRIMARY EDUCATION (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This scientific article analyzes modern methods and pedagogical approaches aimed at enhancing students' knowledge and activity in primary education. It thoroughly elucidates the significance of innovative technologies, interactive methods, critical thinking development strategies, as well as differential and individual approaches. The article presents theoretical foundations and practical recommendations necessary for fostering active participation, independent learning, and problem-solving skills in the educational process. Special attention is given to the impact of effective assessment and feedback mechanisms on student motivation. Based on the fundamental principles of modern pedagogy, the research offers comprehensive solutions that contribute to improving the quality of primary education.